THE IMPORTANCE AND DEVELOPMENT PROSPECTS OF RECONSTRUCTIVE PLASTIC SURGERY IN CLINICAL PRACTICE - Turayeva Malika Shokirovna (Research Journal of Trauma and Disability Studies, 2025)
Reconstructive plastic surgery plays a critical role in modern clinical practice by addressing a wide range of medical conditions that affect patients’ appearance, function, and psychological well-being. Unlike aesthetic plastic surgery, which is primarily focused on improving appearance, reconstructive surgery aims to restore normal form and function following trauma, congenital anomalies, oncologic resection, or disease-related deformities. This article explores the importance of reconstructive plastic surgery in improving quality of life and functional recovery, with a particular focus on its application in treating facial and cranial injuries, post-burn contractures, cleft lip and palate, and post-mastectomy breast reconstruction.